Training for staff who support students. (26th June 2015) - Flynn, Eleanor; Woodward‐Kron, Robyn; Hu, Wendy
Summary: Background: Front‐line administrative, academic and clinical teaching staff often find themselves providing pastoral and learning support to students, but they are often not trained for this role, and this aspect of their work is under‐acknowledged. Context: Staff participating in an action research study at two medical schools identified common concerns about the personal impact of providing student support, and of the need for professional development to carry out this responsibility. This need is magnified in clinical placement settings that are remote from on‐campus services. Innovation: Informed by participatory action research, brief interactive workshops with multimedia training resources were developed, conducted and evaluated at eight health professional student training sites. These workshops were designed to: (1) be delivered in busy clinical placement and university settings; (2) provide a safe and inclusive environment for administrative, academic and clinical teaching staff to share experiences and learn from each other; (3) be publicly accessible; and (4) promote continued development and roll‐out of staff training, adapted to each workplace (seehttp://www.uws.edu.au/meusupport ). The workshops were positively evaluated by 97 participants, with both teaching and administrative staff welcoming the opportunity to discuss and share experiences. Staff supporting health professional students have shared, often unmet, needs for support themselves Implications: Staff supporting health professional students have shared, often unmet, needs for support themselves. Participatory action research can be a means for producing and maintaining effective training resources as well as the conditions for change in practice. In our workshops, staff particularly valued opportunities for guided discussion using videos of authentic cases to trigger reflection, and to collaboratively formulate student support guidelines, customised to each site.